Multidimensional risk factor analysis of acute low back pain progressing to chronicity: a longitudinal cohort study protocol - Huang, Yilong; Li, Chunli; Chen, Jiaxin; Jiang, Yuanming; Yang, Yingjuan; Yang, Juntao; Wang, Zhongwei; Zhao, Derong; Luo, Mingbin; Pu, Fushun; Zhang, Zhenguang; He, Bo (Frontiers in Medicine, 2023)
Introduction Approximately 40% of patients with acute low back pain (LBP) develop chronic low back pain, which significantly increases the risk of poor prognosis. To reduce the risk of acute LBP becoming chronic, effective preventive strategies are needed. Early identification of risk factors for the development of chronic LBP can help clinicians choose appropriate treatment options and improve patient outcomes. However, previous screening tools have not considered medical imaging findings. The aim of this study is to identify factors that can predict the risk of acute LBP becoming chronic based on clinical information, pain and disability assessment, and MRI imaging findings. This protocol describes the methodology and plan for investigating multidimensional risk factors for acute LBP becoming chronic, in order to better understand the development of acute LBP and prevent chronic LBP. Methods: This is a prospective multicenter study. We plan to recruit 1000 adult patients with acute low back pain from four centers. The study will use a longitudinal cohort design. Patients will undergo baseline assessments upon admission and will be followed up for 2 years to collect the time of chronicity and associated risk factors. Upon admission, patients will be collected detailed demographic information, subjective and objective pain scores, disability scale, and lumbar spine MRI scanning. In addition, patient's medical history, lifestyle, psychological factors will be collected. Patients will be followed up at 3 months, 6 months, 1 year, and 2 years after admission to collect the time of chronicity and associated factors. Multivariate analysis will be used to explore the multidimensional risk factors affecting the chronicity of acute LBP patients (such as age, gender, BMI, degree of intervertebral disc degeneration, etc.), and survival analysis will be performed to explore the impact of each factor on the time of chronicity. Ethics and dissemination: The study has been approved by the institutional research ethics committee of each study center (main center number: 2022-L-305). Results will be disseminated through scientific conferences and peer-reviewed publications, as well as meetings with stakeholders.